FONOLOGI BAHASA MINANGKABAU: KAJIAN TRANSFORMASI GENERATIF - Rona Almos (Jurnal Elektronik WACANA ETNIK, 2012)
Regional language spoken in the archipelago according to the national language policy serves as one of the elements of national culture and protected by the state. One of the local languages in Indonesia is the language of Minangkabau. The paper focuses on two issues: 1) how the realization of the original segment morphemes Minangkabau language?, 2) how the processes and phonological rules Minangkabau language?             Phonemic, Minangkabau language has five vowels segments, namely / a, i, u, e, o /. However, phonetic, Minangkabau language has nine vowels because vowels / a, i, u, e, and o / experience the relaxation process each has allophones [I, U, ε, ɔ]. In phonemic consonant number of Minangkabau origin amounted to 18 pieces / p, b, t, d, c, j, k, g, r, l, s, h, m, n, ŋ, ñ,, w, y / , but phonetically Minangkabau language has 19 consonants sound, example; p, b, t, d, c, j, k, g, r, l, s, h, m, n, ŋ, ñ, ʔ, w, y /. Thus, the number of segments in the Minangkabau language vowels and consonants both phonemically is 23 pieces, while as many as 28 segments phonetically.             To explain the changes that occur from the realization of phonemic to phonetic, phonology rules would require eight. Eighth phonology rules include: (1) vocal loosening rules, (2) rule "pelesapan" consonant / h /, (3) rules "pelesapan" resonant sounds / p, t, k, s, c /, (4) additional rules semivokal / w / and / y /, (5) the addition rule consonants / l /, (6) the addition rule consonants / r /, (7) changes in the rules of the consonant / h /, and (8) rule changes kosonan / k/